Semiconductor detector systems - Spieler, Helmuth (Series on semiconductor science and technology ;, 2005)
Semiconductor sensors patterned at the micron scale combined with custom-designed integrated circuits have revolutionized semiconductor radiation detector systems. Designs covering many square meters with million of signal channels are now commonplace in high-energy physics and the technology is finding its way into many other fields, ranging from astrophysics to experiments at synchrotron light sources and medical imaging. This book is the first to present a comprehensive discussion of the many facets of highly integrated semiconductor detectors systems, covering sensors, signal processing, transistors, and circuits, low-noise electronics, and radiation effects. The diversity of design approaches is illustrated in a chapter describing systems in high-energy physics, astronomy, and astrophysics. Finally, a chapter "Why Things Don't Work" discusses common pitfalls. Profusely illustrated, this book includes comprehensive discussions of sensors, signal processing, and electronics, including fine tutorial material, and provides a unique reference in a key area of modern science